KARAKTERISTIK KARBON AKTIF DARI PEMANFAATAN LIMBAH TANAMAN KELAPA SAWIT DENGAN PENAMBAHAN AKTIVATOR NATRIUM KARBONAT (Na2CO3) DAN NATRIUM KLORIDA (NaCl) - Gewa Handika, Seri Maulina, Vidyanova Anggun Mentari (Jurnal Teknik Kimia USU, 2017)
Oil palm tree can produce 22 oil palm frond / year, the average weight of frond per rod reaches 2.2 kg, so that each hectare can produce fresh frond about 9 tons / year or equivalent to 1.64 tons / year of dry matter. Activated carbon can be used as a good absorbent agent for gas purification process and removal of organic pollutants from water, such as in liquid waste. The objective of this paper is to know the different characteristics of activated carbon from oil palm frond (elaeis guineensis jacq) as raw material with variation of activator sodium carbonate (Na2CO3) and sodium chloride (NaCl). The activator concentration used is 10% each with an activation temperature of 600 ° C. The quality of activated carbons was analyzed by surface active carbon morphology and FTIR spectra analysis on activated carbon. The result of identification with FTIR spectrophotometer showed that the activated carbon in this study contained the functional groups of O-H, C = O, C = C, C-C, and C-H.